The Idealism of Unmarried Working Women from a Communication Perpective - Litha, Trianna Sampe (Journal of Feminism and Gender Studies, 2024)
The expectation that demands end when marriage will end for women is no longer commonplace. As time goes by, this choice is increasingly not realized, especially for women because they now strive for success in education and work rather than getting married. It is inevitable that stereotypes about unmarried women are increasingly being expressed, but that does not change their decision. The aim of this research is to understand and describe how working women who decide to be single or not marry communicate. In line with that, this research uses symbolic interaction theory and standpoint theory to explain the idealism of unmarried working women from a communication perspective. This research was conducted using a phenomenological method where interviews were conducted with several informants who were determined based on purposive sampling and snowball sampling techniques. From the research results, it was found that the idealism of women who choose to work rather than marry is entirely based on internal reasons for women who have rights to their own lives and choose not to marry. They said that there was no special and strong reason why women had to get married. Apart from that, getting married is not a priority in life and there is an unpreparedness to be in a long relationship. Apart from that, their quality of life is fine without their married status.